Nu’usi und Nggela, Salomonen. Neue archäologische Forschungen auf den Salomonen Inseln. Die Ergebnisse der Feldkampagnen 2020 und 2021 - Bemama, Grinta; Gegeu, Reubenson; Kiko, Lawrence; Manebosa, Stephen; Moser, Johannes (e-Forschungsberichte des DAI, 2021)
The current research project is designed to focus on archaeological investigations on the pre- and protohistory of the Solomon Islands. In 2020 and 2021, two new research programs were initialized and field work was conducted on the island of Nu’usi in the Maramasike Passage and on the Nggela Island group in Central Province. The archaeological survey on Nu’usi yielded various features in terms of deposited flint nodules, zones of waste flakes and lithic core adzes as indications of knapping activities from the tool production and also architectural structures such as artificial heaps and footpaths. The archaeological survey on Nggela Island resulted in the discovery of eight caves and ten rock shelters. A great number of these sites are showing evidences of human presence in prehistoric times.